Controlling preharvest maturity in farmed Arctic char: A review from the Canadian perspective. Issue 5 (27th May 2019) - Yossa, Rodrigue; Bardon‐Albaret, Agnès; Chiasson, Marcia A.; Liu, Qi; Duston, Jim; Manning, Tony; Benfey, Tillmann J.
Abstract: Arctic char, Salvelinus alpinus L. is a promising candidate for aquaculture expansion in Northern Europe, Canada, and the United States because of its excellent growth at low temperature, tolerance to high rearing density, high fillet yield, and superior flesh texture and flavor. To support this industry, several breeding programs in these regions currently focus on selection for growth and delayed maturation. While the growth potential of existing strains has been improved, preharvest sexual maturation remains a problem in this industry. This article describes current knowledge on the control of preharvest maturation in Arctic char at the hatchery level through the production of single‐sex and triploid populations and during the grow‐out phase through the manipulation of photoperiod and feed intake. Research perspectives on the subject are also suggested in order to complement the efforts of ongoing breeding programs.